Performance Evaluation of Distributed Superconducting Magnetic Energy Storage System (D-SMES) for Power and Frequency Control - Ali Heydarzadegan6 and Hossein Sedaghati, Reza Sedaghati1, Navid Mehdizadeh Afrooz Ahmad Rohani4, Yaser Nemati (International Journal of Scientific Research and Management (IJSRM), 2013)
In this paper, the structure of Distributed Superconducting Magnetic Energy Storage System (D-SMES) is proposed in order to power and frequency control. The main parts that a D-SMES consists of, the various configurations and operational techniques are discussed. The advantages and disadvantages of superconducting energy storage compared with other solutions are provided. Using DSMES allows utilities to improve system reliability and transfer capacity, giving cost-effective grid stabilization for entire electric utility systems. To demonstrate this ability of a D-SMES device, simulations were performed using the MATLAB software. The simulation results are provided and discussed.